THE ROLE OF INDIA IN THE FORMATION OF THE SOUTH ASIAN ASSOCIATION FOR REGIONAL COOPERATION (SAARC) - Syaharani, Elly (Satmata: Journal of Historical Education Studies, 2025)
The purpose of this study is to analyze India's role in the establishment of the South Asian Association for Regional Cooperation (SAARC) and India's involvement in responding to socio-political dynamics in South Asia. The method used is a literature study, collecting data by examining various written sources such as books, literature, notes, and reports relevant to the topic discussed. This literature study research method has the following research system: (1) Problem identification, which is determining the issues or phenomena to be studied, (2) Data collection from literature, which is searching for and collecting data from various references such as books, journals, documents, archives, magazines, or other sources, (3) Classification and evaluation of sources, which involves critiquing and assessing the quality of primary and secondary sources, (4) Data analysis, which involves interpreting the data obtained to answer the research questions, and (5) Drawing conclusions, which involves formulating the research results based on the analysis of the sources reviewed. The results of the study show that India has utilized its position as the country with the greatest political, demographic, and economic power in the region to play a central role in the formation of SAARC. The moderate and open attitude of Indian leaders towards neighboring countries has also encouraged the achievement of regional cooperation consensus. Thus, India has become a major actor contributing to the process of South Asian integration through the formation of SAARC.